PENGARUH PEMANFAATAN PERANGKAT TEKNOLOGI INFORMASI DAN KOMUNIKASI TERHADAP PENINGKATAN KOMPETENSI PROFESIONAL GURU SEKOLAH DASAR - Yohannes Marryono Jamun; Zephisius Rudiyanto Eso Ntelok; Rudolof Ngalu (PGSD UNIKA SANTU PAULUS RUTENG, 2020)
The 4.0 industrial revolution era requires teachers to have a number of characteristics to arrange an appropriate learning administration, be able to design learning media by utilizing Information and Communication Technology (ICT) devices wisely, effectively, competently and professionally. However there are still many problems that hamper the implementation of teacher professional competence in the field of ICT. This study aims to determine whether there is a positive or significant effect between the use of ICT devices on improving teacher professional competence. This type of research is correlational with a quantitative approach. The population of this study were35 elementary school teachers. Data were collected through questionnaire technique. The results of this study indicate that there is a positive and significant influence between the use of ICT devices on increasing the professional competence of group of Elementary School Teachers, with 0.60correlation coefficient. T test results show that tcount>ttable which is 4.31> 2.235. The contribution of ICT tools use to the improvement ofprofessional competence of group of elementary school teachers at Ruteng is 36.05% and 63.95% is influenced by other variables which were not examined by researchers.